EU’s Humanitarian and Civil Protection Aid. Italy’s Eccentric and ECHO-consistent Policy - Fulvio Attinà (Romanian Journal of European Affairs)
This paper analyses the coherence of the aid to countries in need of humanitarian and civil protection assistance given separately by ECHO and the EU Member States, with an emphasis on Italy that appears as an eccentric case. Section one is about the humanitarian aid burden of the EU and the major European donor countries in the years 1999-2012. The analysis draws attention to the existing coherence at the world level and also to the difference existing in the aid to the countries of the Middle East and North Africa region. Section two analyses and shows the consistency of Italy’s aid with the ECHO’s. In the Conclusions, the coherence of the EU’s and states’ aid and the consistency of Italy’s aid are shortly discussed in view of the existing shared powers in the humanitarian and civil protection policy area.